Islamic Feminist Thought: The Contributions of Fatima Mernissi 1940-2015 - Shahin, Farah (El Tarikh : Journal of History, Culture and Islamic Civilization, 2024)
This study explores the dynamic and diverse Islamic feminist movement, which aims to promote justice and gender equality by challenging patriarchal interpretations of Islamictexts and customs. Through the work of scholars such as Fatima Mernissi, this research highlights how Islamic feminism seeks to reinterpret Islamic theology and practice to uphold the rights and dignity of women. Using exploratory and historical qualitative methods, this research evaluates the significant contribution of Islamic feminists in challenging existing discourse and improving the status of women. This study examines the contributions of Islamic feminists in Morocco and the Arab world, focusing on their efforts to promote gender equality within an Islamic framework. by investigating Fatima Mernissi's work which emphasizes the need to re-read Islam's sacred texts and expose false and misogynistic hadith. Apart from that, the influence of Kecia Ali's thoughts in "Sexual Ethics and Islam" as well as the critical views of Asma Barlas, Leila Ahmed, and Amina Wadud regarding misinterpretations of the Koran enrich this research so that it provides a comprehensive view. She argues that Fatima Mernissi's works, by offering alternative readings of Islamic discourse on women, have advanced feminist debate and practice in the Arab world, enriching understanding of faith, gender, identity and culture in Islam.